Successful treatment of KPC-MDR septic shock with ceftazidime-avibactam in a pediatric critically ill patient. (2019) - Vargas, Maria; Buonomo, Antonio Riccardo; Buonanno, Pasquale; Iacovazzo, Carmine; Servillo, Giuseppe
Abstract: Ceftazidime–avibactam is a combination agent consisting of the β-lactamase inhibitor avibactam and the broad-spectrum cephalosporin ceftazidime. There are no published case reports or studies evaluating the use of CAZ-AVI in pediatric critically ill patients. We report a case of a successful treatment of septic shock due to Klebsiella pneumonie (KP) in a 14-years-old boy (body weight 50 kg) admitted in intensive care unit (ICU).